Prevalence of microalbuminuria in patients with non-diabetic acute ischemic stroke - N, Muralidhara; Rajanna, Ravindra; Varakanahalli, Shivakumar; Goyal, Vijay Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Microalbuminuria has been associated with clinical risk factors for stroke like diabetes, hypertension, aging, history of myocardial infarction, obesity, smoking and left ventricular hypertrophy. The present study is aimed to determine the potential use of microalbuminurea, as a marker of stroke risk and its outcome in non-diabetic population. Methods: The present study was conducted in the department of internal medicine and department of neurology after the institutional ethical clearance and the informed consent from all the subjects. A total of 116 patients admitted with acute ischemic stroke presenting within 24 hours of stroke onset were recruited for the study. The microalbuminurea was assayed by immunoprecipitation. The stroke severity was assessed by NIH Stroke Severity Statistical Software Package. P value less than 0.05 was considered the level of significance. Results: There was graded co-relation between NIHSSS score and urine albumin creatinine ratio with significant P value of <0.001 in group A, but no such co-relation was seen in group B (P value 0.2). This suggests more the elevated urine ACR more the neurodefecit implying its utility as prognostic marker in acute ischemic stroke. Conclusion: Urine albumin excretion had the strongest correlation with the NIHSSS Score of the patient in acute ischemic stroke. Therefore, measurement of microalbuminurea may help to assess those who are at increased risk and to triage those who may need a more aggressive management protocol.